Effect of Hydrothermal Treatment on selected Properties of Cocoyam Corm (colocasia esculenta) Flour - Asema, Kator; Adejumo, Bolanle Adenike (Indonesian Food Science and Technology Journal, 2022)
The aim of this work is to evaluate the effect of hydrothermal treatment on the physicochemical properties of cocoyam flour. Harvested cocoyam (Colocasia esculenta) was sorted, peeled, washed, sliced, washed, blanched at temperature 60 ÌŠ C, 80 ÌŠ C and 100 ÌŠ C and soaked at different time of 12 hours, 24 hours and 48 hours after then oven dried. The dried samples were milled into flour labelled A, B, and C at three replicates (3Ã—3Ã—3=27) with unblanched and unsoaked sample D as control. The samples were packaged for analysis. Result showed that at temperature 60 ÌŠ C for soaking time 12 hours, 24 hours and 48 hours, the moisture content are 4.16 %, 3.62 % and 5.01 %, fat 5.22 %, 5.22 % and 4.72 %, crude fibre 0.98 %, 0.99 % and 0.53 %, protein 1.75 %, 1.47 % and 1.61 %. It is concluded that hydrothermal treatment of cocoyam (colocasia esculenta) can modify the physicochemical properties of flour produced. However, the minimum effect occurred at 60 ÌŠ C compared to 80 ÌŠ C and 100 ÌŠ C .thus, the quality of cocoyam flour can be improved using blanching temperature 60 ÌŠ C and 12 hours soaking time.